Kinetic and in situ FTIR study of CO methanation on a Rh/Al2O3 catalyst1. Issue 9 (17th September 2015) - Escobar, Mauricio; Gracia, Francisco; Karelovic, Alejandro; Jiménez, Romel
<x xml:space="preserve">Abstract</x> Carbon monoxide hydrogenation was studied over a γ-alumina-supported 1 wt% Rh catalyst by means of kinetic and in situ infrared measurements.